Implications of Capital Adequancy Ratio (CAR), Loan To Deposit Ratio (LDR), and Financial Performance - Wedaswari Made; Purwanto Purwanto; Sari Widati; Eka Nur Haini Widyaningrum (Universitas Veteran Bangun Nusantara, 2024)
The aim of this research is to determine the effect of capital adequacy ratio and loan to deposit ratio on financial performance with credit risk as a moderating variable and it is hoped that the results of this research can be used as a reference source for potential investors before investing their capital in banking companies, especially conventional banks by analyzing how banking financial performance and health. In this research the data used is secondary data. The research method uses a multiple analysis method using the IBM SPSS Statistics version 22.0 and Microsoft Excel 2010 programs. The data collection technique uses a purposive sampling technique with a population of 46 conventional banks becoming 36 research samples. This research uses the unit of measurement of percent (%) obtained from the company's annual report. Before multiple linear analysis is carried out, it is tested first with the classic assumption test which is useful for ensuring whether the regression model used does not have problems with normality, muticolinearity, heteroscedasticity and autocorrelation tests. If it is fulfilled then the multiple regression model is suitable to be used. The research results show that the capital adequacy ratio and loan to deposit ratio have a significant positive effect on financial performance. Moderation regression analysis, credit risk as proxied by non-performing loans is not able to moderate the relationship between capital adequancy ratio and loan to deposit ratio on financial performance.